A New model for Alloxan-induced diabetes mellitus in rats - Sheriff, Ojulari Lekan; Olayemi, Oladeru; Taofeeq, Ayinde Olanrewaju; Riskat, Kadir Eniola; Ojochebo, Dangana Elizabeth; Ibukunoluwa, Alade Olusoji (Journal of Bangladesh Society of Physiologist, 2020)
Background: Alloxan is widely used to induce experimental diabetes mellitus (DM) in animals with different grades of disease severity by varying the dose of Alloxan used. This method has however be questioned by recent research work as an appropriate technique for the induction of diabetes. Objective: To provide a simple, yet concise and reproducible experimental procedure and model for Alloxan-induced DM in rats. Methods: The study was divided into 2 separate experiments. Experiment 1: Alloxan was administered, into four subgroups each (group 1- 100 mg of Alloxan /kg of rat body weight, group 2- 120 mg/kg, group 3- 150 mg/kg, and group 4- 170 mg/kg); in each subgroup, the dose of Alloxan was administered at different concentrations (20 mg/ml, 10 mg/ml, 5 mg/ml and 4 mg/ml) in groups of 10 rats each. The pre-induction fasting period was also varied between groups. Experiment 2:Following a pre-induction fasting period of 36 hours, animals received 150 mg Alloxan /kg body weight and at a concentration of 20 mg Alloxan/ ml. Result:Alloxan administered intraperitoneally at 150 mg/kg of rat body weight, at 20 mg/ml and following a pre-induction fast period of 36 hours yielded the most favorably conditions with the least recorded mortality. Conclusion: From the results of this study, it can be concluded that alloxan is a diabetogenic drug with a strict protocol of use in inducing a predictable DM in rats and as such, this model is a standard and reproducible technique for the induction of DM in experimental rats. J Bangladesh Soc Physiol. 2019, December; 14(2): 56-62